The glymphatic system: a new perspective on brain diseases - Ding, Zhao; Fan, Xiaodi; Zhang, Yehao; Yao, Mingjiang; Wang, Guangrui; Dong, Yilei; Liu, Jianxun; Song, Wenting (Frontiers in Aging Neuroscience, 2023)
The glymphatic system is a brain-wide perivascular pathway driven by aquaporin-4 on the endfeet of astrocytes, which can deliver nutrients and active substances to the brain parenchyma through periarterial cerebrospinal fluid (CSF) influx pathway and remove metabolic wastes through perivenous clearance routes. This paper summarizes the composition, overall fluid flow, solute transport, related diseases, affecting factors, and preclinical research methods of the glymphatic system. In doing so, we aim to provide direction and reference for more relevant researchers in the future.